Cert Prep: SOLIDWORKS Drawing Tools. - Corbett, Gabriel (linkedin.com, 2017)
Study to pass the CSWPA-DT (Certified SOLIDWORKS Professional Advanced Drawing Tools) exam and earn proof of your SOLIDWORKS expertise.